2021
DOI: 10.3390/coatings11070857
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Plasma Coatings on Orthodontic Brackets: In Vitro Metal Ion Release and Cytotoxicity

Abstract: The metal ion release characteristics and biocompatibility of meta-based materials are key factors that influence their use in orthodontics. Although stainless steel-based alloys have gained much interest and use due to their mechanical properties and cost, they are prone to localised attack after prolonged exposure to the hostile oral environment. Metal ions may induce cellular toxicity at high dosages. To circumvent these issues, orthodontic brackets were coated with a functional nano-thin layer of plasma po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These coated brackets showed only minimal metal ion leak in comparison to the untreated ones. Moreover, in the cytotoxicity assessment, decrease in viability of the fibroblast was not observed [ 239 ].…”
Section: Orthodonticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These coated brackets showed only minimal metal ion leak in comparison to the untreated ones. Moreover, in the cytotoxicity assessment, decrease in viability of the fibroblast was not observed [ 239 ].…”
Section: Orthodonticsmentioning
confidence: 99%
“… Schematic illustration of the design of surface-functionalized orthodontic brackets involving plasma coating and subsequent immobilization with enantiomers of amino acid to combat metal ion release [ 239 ] Reprinted with permission from Kumarasinghe et al, Coatings; published by MDPI, 2021. …”
Section: Figurementioning
confidence: 99%
“…Thus, the spiropolymers P1a3f and P1a3f-SH have potential applications in gastric medicine. Cell experiments indicated that P1a3d, P1a3f, and P1a3f-SH had low cytotoxicities to NIH 3T3 and HeLa cells at low concentrations due to their spiro-(benzo)furanone skeletons, 41 no heavy atoms such as metals, 63 and no charge (Figures S42 and S43), 64 suggesting that the spiropolymers have good biocompatibility before and after acid hydrolysis.…”
Section: Solubility and Thermal Stabilitymentioning
confidence: 99%
“…Further attempts regarding polymer-based coatings deposited onto fixed orthodontic metallic components include: (i) 2-methacryloyloxyethyl phosphorylcholine: an hydrophilic and antibacterial phospholipid polymer with low friction property, which reduced the CoF of coated SS wires against brackets, and inhibited the in vitro adhesion of S. mutans and P. aeruginosa [510]; (ii) butyl-3-methylimidazolium chloride, which reduced the in vitro corrosion of NiTi archwires in fluoride-and/or bovine albumin-containing artificial saliva; (iii) 1H,1H,2H,2H-perfluorodecyltrimethoxysilane with bovine serum albumin, showing a non-bactericidal but highly antibacterial effect by preventing adhesion through a protein-mediated mechanism [513]; (iv) polydopamine and carbon dots: a fluorescent and antibacterial coating, with in vitro cytocompatibility, deposited on SS brackets [515]; (v) polyoxazoline with tryptophan coating, which decreased metal release and showed good in vitro biocompatibility to primary human dermal fibroblasts [512]; and (vi) silicone coatings on β-Ti and SS archwires [506].…”
mentioning
confidence: 99%